Hubungan antara total asupan energi dan komponen makrontrien dengan penambahan berat badan ibu hamil di Kecamatan Pedurungan Kota Semarang - Astuti, Yuli; Hidayat, Yudi Mulyana; Rohmawati, Enny (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Gestational weight gain (GWG) is physiological change in pregnancy. Inadequate gestational weight gain (IGWG) and excessive gestational weight gain (EGWG) can pose a risk of complication such as gestational hypertention, low birth weight, giant baby, and premature birth. Food intake (energy and macronutrient) play important role in providing pregnancy needs such as fetal and placental growth, and also play role in fat accumulation in some part of mother’s body. Objectives: This study aims to analyze the relationship between energy intake and macronutrient and gestational weight gain of pregnant woman and to know the consumption of food groups.Methods: This study was quantitative study using cohort prospective approach. 73 healthy pregnant women with normal body fat mass who met inclusion and exclusion criteria was weighed twice in a period of 8 weeks. 24 hours food recall in 2 unsecutive days was done between those times. The instruments used for this study were weight scale, stadiometer, and questionnaire. Nutritional analysis used Nutrisurvey and statistic analysis used Chi Square test.Result: There was a relationship between total energy intake and gestational weight gain ( p = 0.031) and there was no relationship between macronutrient component intake (carbohydrate, fat, and protein) and gestational weight gain (p = 0.175, p = 0.97, and p = 0.089 respectively). Respondent characteristic that has corelation with GWG is number of pregnancy. Most pregnant woman experienced EGWG (56.2%) and their food consumption not fulfilled the balance nutrient recommendation guidelines especially less in vegetables and fruits consumption.Conclusion:There is a significant corelation between energy intake and GWG.